Reconstructing the sequence of massive rock-slope failures in Valle di Tovel, Trentino (Italy) - Susan Ivy-Ochs; Alfio Viganò; Sandro Rossato; Silvana Martin; Christof Vockenhuber; Manuel Rigo; Paolo Campedel (2018)
Symposium Quaternary environmentsPlatform Geosciences, Swiss Academy of Science, SCNAT Swiss Geoscience Meeting 2018 P 11.14: Reconstructing the sequence of massive rock-slope failures in Valle di Tovel, Trentino (Italy) Susan Ivy-Ochs 1, Alfio Viganò 3, Sandro Rossato 2, Silvana Martin 2, Christof Vockenhuber 1, Manuel Rigo 2, Paolo Campedel 31 Using field mapping, remote imagery interpretation (2 m lidar kindly provided by the Autonomous Province of Trento) and cosmogenic 36Cl exposure dating we reconstruct the origin of the blocky deposits in the upper reaches of the Valle di Tovel in the Adamello Brenta Geopark in the Brenta Dolomites. Blocky deposits cover nearly the whole valley floor for a length of about 10 km from an elevation of 1900 down to 900 m a.s.l. Oetheimer (1992) estimated a total volume of more than 300 Mm3. Although several independent bodies, sourced in the steep surrounding rock walls which reach up to 2700 m a.s.l., are apparent (Oetheimer 1992, Ferretti and Borsato 2004) detailed reconstruction of the timing and sequence of the catastrophic events is challenging. Hypotheses for the age and origin of the blocky deposits range from a Lateglacial rock-slope failure onto a glacier (Oetheimer 1992) to mainly 16th century events. At that time, blocking of the outflow led to lake level rise of about 18 m as shown by dendrochronological ages of drowned trees, many of which are still standing on the lake bottom. The lake itself is renowned for the red color due to algal bloom it had during summers up until 1964 (Kulbe et al. 2005). Interpretation of the evolution of the valley involves disentangling the numerous interfering deposits of megablocks released intermittently from the exceptionally steep valley walls. Although there are distinct differences in the amount of vegetation in the different sectors this is clearly not directly translatable into age, and other factors may play just as important a role. Present permafrost is likely restricted to ridge tops above about 2500 m a.s.l. (Boeckli et ...